2009
DOI: 10.2304/pfie.2009.7.4.399
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Academic Achievement and Their Possible Applications

Abstract: A significant amount of attention has been given to the predictors of academic achievement in higher education. However, the vast majority of articles have centred on entrance criteria and the learning approaches or personal habits of students. Investigations into how achievement depends on student efforts, being almost invariably based on subjective and unavoidably imprecise student self-evaluations, do not generally help the university determine how it can actually promote academic achievement. In this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…This is the rst time that this has been shown for nursing students or in a pharmacology course. However, this nding is not consistent for all disciplines, as marked tutorials have been shown to improve marks for courses in calculus, macroeconomics [16], nance [17], and law [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the rst time that this has been shown for nursing students or in a pharmacology course. However, this nding is not consistent for all disciplines, as marked tutorials have been shown to improve marks for courses in calculus, macroeconomics [16], nance [17], and law [20].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, marks for home assignments were a strong predictor of examination performance in courses in calculus and macroeconomics [16], and education [17]. Marks for home assignments in statistics were shown to predict examination performance in one study [18], but not another [16]. Other studies have shown that marked tutorial-based assessments have a signi cant positive association with examination performance in nance [19] and law [20] courses.…”
Section: Introductionmentioning
confidence: 99%
“…Only in one course of this study, was the ongoing assessment marks separated, and this showed no correlation between the marks for a practical write-up and an aligned examination question [13]. In contrast, marks for home assignments were a strong predictor of examination performance in courses in calculus and macroeconomics [16], and education [17]. Marks for home assignments in statistics were shown to predict examination performance in one study [18], but not another [16].…”
Section: Introductionmentioning
confidence: 55%
“…However, this finding is not consistent for all disciplines or students. Marked tutorials improved marks in examination for courses in calculus, macroeconomics [16], finance [20], and law [21]. Marked homework in statistics has been variously shown to improve examination performance [18] or have no effect [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation